Physicochemical properties of peanut oil body nutritional emulsions: effects of energy density and nutrient ratio - Lin, Zihui; Zhao, Zhihao; Zhou, Pengfei; Deng, Yuanyuan; Liu, Guang; Li, Ping; Zeng, Jiarui; Xiang, Fahui; Pang, Jie; Zhang, Mingwei (Frontiers in Sustainable Food Systems, 2025)
The physical and chemical stability of peanut oil body (POB) nutritional emulsions and traditional emulsifier-based nutritional emulsions were compared under varying energy densities and nutrient ratios, with a focus on protein adsorption at the oil-water interface. The results demonstrated that flocculation was the primary instability mechanism for POB emulsions, whereas emulsifier-based emulsions predominantly experienced coalescence. At energy densities of 1.9 and 2.1 kcal/mL, POB nutritional emulsions exhibited lower PDI values (0.136 and 0.139), compared to emulsifier-based emulsions (0.152 and 0.191). Additionally, micromorphology analysis indicated enhanced anti-coalescence properties for POB emulsions. The interfacial protein adsorption capacity of POB emulsions (6.8 and 7.0 mg/m2) was also lower than that of emulsifier-based emulsions (7.5 and 8.0 mg/m2), suggesting that the thinner interfacial protein film may contribute to the improved storage stability of POB emulsions. At an energy density of 2.1 kcal/mL, after adjusting the nutrient ratio, the CI values of POB emulsions (8.79%, 3.95%, 3.75%) were consistently lower than those of emulsifier-based emulsions (10.25%, 8.16%, 8.02%), further indicating superior storage stability. Both emulsions showed similar appearance colors. These findings demonstrate that POB emulsions offer a promising alternative to refined oil in nutritional emulsion formulations, effectively replacing traditional emulsifiers, particularly in high-energy-density applications.